Dendrobium candidum polysaccharide reduce atopic dermatitis symptoms and modulate gut microbiota in DNFB-induced AD-like mice - Liang, Yiheng; Liu, Guangrong; Xie, Lingna; Su, Kewen; Chang, Xia; Xu, Yani; Chen, Junsong; Zhu, Zhenyuan; Yang, Kaiye; Chen, Huixiong; Du, Zhiyun (Frontiers in Physiology, 2022)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with a high prevalence worldwide. Increasing evidence suggests that the gut microbiota plays an important role in the pathogenesis of AD. In this study, we sought to verify the effect of Dendrobium candidum polysaccharides (DCP) on AD induced by 2,4-Dinitrofluorobenzene (DNFB) in Balb/c mice regarding its impact on the intestinal microbiome. We found that 2-week oral administration of DCP improved AD-like symptoms and histological damage of skin, reduced mast cell infiltration, down-regulated the level of serum total IgE and the expression of pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-4 and IL-6, and increased the expression level of anti-inflammatory cytokine IL-10. The beneficial effect of DCP was attributed to the restoration of the intestinal microbiome composition and the unbalance of the intestinal homeostasis. Our results indicated that DCP might be used as a promising novel microbiota-modulating agent for the treatment of AD.